GCMS analysis and acaricidal activity of Ailanthus altissima extract against cattle tick Rhipicephalus (Boophilus) microplus and Hyalomma anatolicum: in vitro and in silico approach - Shakir Ullah; Nosheen Malak; Afshan Khan; Sadaf Niaz; Raquel Cossío Bayúgar; Imtiaz Ahmad; Nasreen Nasreen; Nadia Bibi; Mourad Ben Said; Adil Khan; Denekew Temesgen; Most. Nazmin Aktar; et al. (Scientific Reports)
Abstract Ticks, hematophagous ectoparasites, pose significant health risks to wildlife and humans as vectors for various pathogens. This study aims to assess the efficacy of Ailanthus altissima plant extract against Rhipicephalus (Boophilus) microplus and Hyalomma anatolicum ticks using both in vitro and in silico approaches. According to gas chromatography–mass spectrometry, 29 bioactive components with varying retention times have been identified in the methanol leaf extract of A. altissima. The plants methanolic extracts were prepared, subsequently diluted to concentrations of 25, 50, 75, and 100 mg/mL. Ticks underwent an adult immersion test (AIT) to evaluate extract effectiveness. AIT results were statistically analyzed via probit regression for lethal concentration (LC50 and LC90) and lethal time (LT50 and LT90) values. Three-dimensional structures of R. (B.) microplus acetylcholinesterase (RmAChE) and H. anatolicum glutathione S-transferase (HaGST) were modeled using homology modeling, validated through Ramachandran plots and ERRAT server. Molecular docking studies explored extract inhibitory mechanisms at the molecular level against RmAChE (4-Quinolinecarboxylic acid: − 6.6 kcal/mol) and HaGST (Gamma Tocopherol: − 6.6 kcal/mol). In vitro findings indicated superior efficacy of the plant extract compared to the positive control permethrin (a commercially available acaricide), a result supported by in silico studies showing several phytochemicals with inhibitory potential against these tick species.